红仁核桃多肽的制备工艺优化及降血脂功能研究Optimization of the preparation process of red kernel walnut polypeptide and its hypolipidemic effect - 吴淑娟1，王锐2，董兆斌3，夏禹承1，廖玉美4，张润光1，张有林1 WU Shujuan1, WANG Rui2, DONG Zhaobin3, XIA Yucheng1, LIAO Yumei4, ZHANG Runguang1, ZHANG Youlin1 (Zhongguo youzhi, 2023)
为对红仁核桃的精深加工及其保健功能提供参考，以红仁核桃分离蛋白为原料对其进行酶解制备红仁核桃多肽，采用单因素试验和正交试验优化酶解工艺条件，并经超滤分离得到3个组分的红仁核桃多肽，测定其多肽含量、胰脂肪酶抑制率和胆固醇胶束溶解度抑制率。以高血脂SD大鼠为模型，分别以活性最高的红仁核桃多肽的低、中、高剂量（200、400、800 mg/kg）饲喂大鼠28 d，测定大鼠体质量、脏器质量和血清指标，并进行组织切片观察。结果表明：红仁核桃多肽制备的最佳条件为酶解pH 9.0、底物质量分数4.0%、酶加入量（以反应体系总质量计）4.0%、酶解温度55 ℃，在此条件下水解度达到6.96%；分子质量小于3 kDa的组分活性最高；用红仁核桃多肽灌胃SD大鼠后能显著减缓大鼠体质量及肝脏、肾脏和附睾脂肪组织质量的增加（p<0.05），显著或极显著降低大鼠血清总胆固醇含量、甘油三酯含量、低密度脂蛋白胆固醇含量、动脉粥样硬化指数，升高高密度脂蛋白胆固醇含量（p<0.05，p<0.01）；组织切片观察结果显示仁核桃多肽干预能抑制脂肪组织的生长和积累。红仁核桃分离蛋白酶解产物多肽具有较好的降血脂功能。 In order to provide reference for the deep processing and health function of red kernel walnut, the red kernel walnut polypeptide was prepared by the enzymatic hydrolysis of red kernel walnut protein isolate, the single factor test and orthogonal test were used to optimize the enzymolysis process conditions. Three components of red kernel walnut polypeptide were separated by ultrafiltration, and its polypeptide content, the inhibition rates of pancreatic lipase and cholesterol micelle solubility were measured. Taking hyperlipidemia SD rats as a model, and low, medium, and high doses (200,400,800 mg/kg) of red kernel walnut polypeptide with the highest activity were administered to the rats for 28 d, and the body weight, organ weight, serum biochemical indicators of rats were measured and the tissue sections were observed. The results showed that the optimal conditions for the preparation of red kernel walnut polypeptide were as follows: enzymatic pH 9.0, mass fraction of substrate 4.0%, enzyme addition amount (calculated by the total mass of the reaction system) 4.0%, and enzymatic temperature 55 ℃. Under these conditions, the degree of hydrolysis was 6.96%. Components with molecular mass less than 3 kDa had the highest activity. Red kernel walnut polypeptide gavage significantly reduced the increase of body weight and mass of liver, kidney and epididymal adipose tissue in SD rats(p<0.05), and serum total cholesterol, triglycerides, low-density lipoprotein cholesterol and arterisclerosis index were significantly reduced in rats, while the high-density lipoprotein cholesterol content was increased (p<0.05,p<0.01). The tissue section observation showed that the intervention of red walnut polypeptide could inhibit the growth and accumulation of adipose tissue. The hydrolyzed polypeptides of red kernel walnut protein isolate have a good hypolipidemic effect.